2016
DOI: 10.1080/14615517.2015.1125643
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of significance in environmental impact assessment

Abstract: Impact significance determination lies at the heart of environmental impact assessment (EIA) but conflict and misunderstanding around the concept is common. This paper attempts to make sense of impact significance in EIA based on four essential components of significance synthesised from the literature to ensure that: (1) a clear operational framework for significance determination applies throughout EIA, (2) attention focuses only on significant issues, (3) the term significance is specified and applied consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
0
13
0
2
Order By: Relevance
“…Thus, they are intended to be advisory units that are more capable to digest large amounts of data and can perform quick computations. Decision-making tends to entail social and political conflicts while also relating to values that reflect cultural, historical and social norms that are deemed acceptable by a community (Jones & Morrison-Saunders, 2016). This is crucial for spatial planning and waste management, which are (1) connected to specific geographical contexts with intrinsic cultural, historical and social values, and (2) directly affect the environment and the society in a given territory.…”
Section: Technology and Analysis Methodsmentioning
confidence: 99%
“…Thus, they are intended to be advisory units that are more capable to digest large amounts of data and can perform quick computations. Decision-making tends to entail social and political conflicts while also relating to values that reflect cultural, historical and social norms that are deemed acceptable by a community (Jones & Morrison-Saunders, 2016). This is crucial for spatial planning and waste management, which are (1) connected to specific geographical contexts with intrinsic cultural, historical and social values, and (2) directly affect the environment and the society in a given territory.…”
Section: Technology and Analysis Methodsmentioning
confidence: 99%
“…However, we found that every EIS relied on the reasoned approach, using professional judgement for the majority, if not all, determinations of impact significance. While using professional judgement is itself not cause for concern, relying on such judgement without clearly outlining the considerations that influence significance determination can undermine transparency (Jones & Morrison‐Saunders, 2016). Furthermore, professional judgement acquired without a structured protocol to counteract cognitive biases and overconfidence in assessment is prone to generating misleading results (Morgan, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…A subset of the impacts identified in an EIS may be classified as ‘significant’. A precise definition of this term is difficult to pin down (Jones & Morrison‐Saunders, 2016), but broadly, significant impacts are those that are thought to cause substantial (usually negative) changes to the natural or human environment. EIS authors will typically explore how significant impacts will be mitigated either during or after the development.…”
Section: Methodsmentioning
confidence: 99%
“…Though quantitative thresholds were sometimes factors in determining the significance of an impact (48% of our sample used quantitative thresholds for a subset of impacts, and 42% did so for a subset of cumulative impacts), we found that every EIS relied on the consultants' judgement for the majority, if not all, determinations of impact significance. While using professional judgement is itself not cause for concern, relying on professional judgement without clearly outlining the considerations that influence significance determination lacks transparency (Jones and Morrison-Saunders 2016). Based on our sample, 69% of EISs did not clearly document the methods used to determine significance, and for the 31% that did, significance was based on ambiguous qualitative criteria with little explicit information on how these were derived or applied.…”
Section: Likely Biased Significance Determinationmentioning
confidence: 87%